An Analysis of the Knowledge-AttitudeBehavior Approach to Personal Data Security Resilience Among Students in West Java - Eka Hidayat (Universitas Multimedia Nusantara, 2026)
Digital transformation in the higher education sector poses significant risks to students' personal data security. Data breach incidents within campus environments demonstrate that state-of-the-art technological infrastructure will not be effective unless complemented by user security awareness. This study aims to analyze the personal data security resilience of students in West Java through the Knowledge-Attitude-Behavior approach. A quantitative survey method was applied to collect and evaluate students' empirical responses regarding their cognitive understanding of cyber risks, emotional responses to privacy policies, and concrete actions in protecting sensitive information. The evaluation results of these three dimensions are expected to measure the readiness and effectiveness of students as the first line of defense, or a human firewall, against various cybercrime threats. The findings of this study are projected to provide an empirical foundation for higher education institutions and policymakers in designing mitigation strategies and comprehensive, sustainable cybersecurity literacy programs.